2001
DOI: 10.1177/00912700122009917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential Pharmacokinetic Interaction between Almotriptan and Fluoxetine in Healthy Volunteers

Abstract: This study was designed to assess the pharmacokinetics of almotriptan, a 5HT1B/1D agonist used to treat migraine attacks, when administered in the presence and absence of fluoxetine. Healthy male (n = 3) and female (n = 11) volunteers received (1) 60 mg fluoxetine daily for 8 days and 12.5 mg almotriptan on Day 8 and (2) 12.5 mg almotriptan on Day 8, according to a two-way crossover design. Plasma and urinary almotriptan concentrations were measured by HPLC methods. Treatment effects on pharmacokinetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…The N-demethylation and N-oxidation of the dimethylaminoethyl group are minor metabolic reactions both in vitro and in vivo. Different clinical trials conducted to study the effect of CYP3A4, CYP2D6, and MAO-A on the pharmacokinetics of almotriptan showed that verapamil and fluoxetine modestly inhibited almotriptan clearance, a result consistent with the assignement of CYP3A4 and CYP2D6 as the enzymes responsible for the oxidation of the pyrrolidine moiety (Fleishaker et al, 2000(Fleishaker et al, , 2001a. Moreover, moclobemide increased plasma concentrations of almotriptan by 37%, thus confirming that oxidative deamination of almotriptan by MAO-A was the major route of metabolism and that the degree of interaction was much less than that seen previously for sumatriptan, rizatriptan, or zolmitriptan given with moclobemide (Fleishaker et al, 2001b).…”
mentioning
confidence: 55%
“…The N-demethylation and N-oxidation of the dimethylaminoethyl group are minor metabolic reactions both in vitro and in vivo. Different clinical trials conducted to study the effect of CYP3A4, CYP2D6, and MAO-A on the pharmacokinetics of almotriptan showed that verapamil and fluoxetine modestly inhibited almotriptan clearance, a result consistent with the assignement of CYP3A4 and CYP2D6 as the enzymes responsible for the oxidation of the pyrrolidine moiety (Fleishaker et al, 2000(Fleishaker et al, , 2001a. Moreover, moclobemide increased plasma concentrations of almotriptan by 37%, thus confirming that oxidative deamination of almotriptan by MAO-A was the major route of metabolism and that the degree of interaction was much less than that seen previously for sumatriptan, rizatriptan, or zolmitriptan given with moclobemide (Fleishaker et al, 2001b).…”
mentioning
confidence: 55%
“…Absorption is rapid, maximal plasma concentration is achieved between 1.5 and 4 h after dose administration; however, after 1 h the plasma concentration is 68% of the Cmax (Fleishaker, Ryan, Carel et al 2001). …”
Section: Pharmacologymentioning
confidence: 99%
“…Almotriptan has been tested for its potential pharmacokinetic interaction with several drugs, including MAO-A inhibitors (Fleishaker, Ryan, Jansat et al 2001), SSRIs (Fleishaker, Ryan, Carel et al 2001), β-adrenergic (Fleishaker, Sisson et al 2001) and calcium channel blocking agents (Fleishaker et al 2000), and ketokonazole (Fleishaker et al 2003), and even though some pharmacokinetic interaction was shown, including an increased plasma concentration of almotriptan, the authors did not find a clinically significant profile. Consequently, no dose adjustment is necessary when almotriptan is taken together with these drugs.…”
Section: Pharmacologymentioning
confidence: 99%
“…The almotriptan drug-drug interaction profile has been evaluated with regard to the calcium (Ca 2þ )-channel blocker verapamil (32), the b-blocker propranolol (33) and the selective serotonin reuptake inhibitor fluoxetine (34), all agents used for migraine prophylaxis, the antifungal agent ketoconazole (35) and the antidepressant moclobemide (36). Propranolol has been shown to inhibit the metabolic pathways of several drugs eliminated by the P450 pathway (37) and shares at least one elimination pathway with almotriptan, CYP2D6.…”
Section: P H a R M A C O L O G Y O F A L M O T R I P T A Nmentioning
confidence: 99%